The generator coordinate Hartree-Fock method as strategy for building Gaussian basis sets to ab initio study of the process of adsorption of sulfur on platinum (200) surface - Treu, O.; Pinheiro, J. C.; Kondo, R. T. (Elsevier B.V., 2005)
The scheme named generator coordinate Hartree-Fock method (GCHF) is used to build (22s14p) and (33s22p16d9f) gaussian basis sets to S ((3)P) and Pt ((3)D) atoms, respectively. Theses basis sets are contracted to [13s10p] and [19s13p9d5f] through of Dunning's segmented contraction scheme and are enriched with d and g polarization functions, [13s10p1d] and [19s13p9d5flg]. Finally, the [19s13p9d5f1g] basis Set to Pt ((3)D) was supplemented with s and d diffuse functions, [20s13p10d5flg], and used in combination with [13s10p1d] to study the effects of adsorption of S ((3)D) atom on a pt ((3)D) atom belonged to infinite Pt (200) surface. Atom-atom overlap population, bond order, and infrared spectrum of [pt(_)S](2 -) were calculated properties and were carried out at Hartree-Fock-Roothaan level. The results indicate that the process of adsorption of S ((3)P) on pt ((3)D) in the infinite Pt (200) surface is mainly caused by a strong contribution of sigma between the 3p(z) orbital of S ((3)P) and the 6s orbital of pt ((3)D). (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Gaussian basis sets; contracted basis sets; GCHF method; adsorption of sulfur on platinum; surface process